2017
DOI: 10.3390/ijms18102220
|View full text |Cite
|
Sign up to set email alerts
|

Argan Oil-Mediated Attenuation of Organelle Dysfunction, Oxidative Stress and Cell Death Induced by 7-Ketocholesterol in Murine Oligodendrocytes 158N

Abstract: Argan oil is widely used in Morocco in traditional medicine. Its ability to treat cardiovascular diseases is well-established. However, nothing is known about its effects on neurodegenerative diseases, which are often associated with increased oxidative stress leading to lipid peroxidation and the formation of 7-ketocholesterol (7KC) resulting from cholesterol auto-oxidation. As 7KC induces oxidative stress, inflammation and cell death, it is important to identify compounds able to impair its harmful effects. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 132 publications
(197 reference statements)
3
38
2
1
Order By: Relevance
“…The lipids were transmethylated using boron trifluoride in methanol, in accordance with Morrison & Smith [ 45 ]. The fatty acid methyl esters were then analyzed under the same conditions as those described by Debbabi et al [ 46 ] and Badreddine et al [ 47 ]. The data were processed with EZChrom Elite software (Agilent Technologies, Massy, France) and are reported in mg/g total lipids.…”
Section: Methodsmentioning
confidence: 99%
“…The lipids were transmethylated using boron trifluoride in methanol, in accordance with Morrison & Smith [ 45 ]. The fatty acid methyl esters were then analyzed under the same conditions as those described by Debbabi et al [ 46 ] and Badreddine et al [ 47 ]. The data were processed with EZChrom Elite software (Agilent Technologies, Massy, France) and are reported in mg/g total lipids.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, the preventive effect of argan oil on hyperinsulinemia and insulin resistance might be associated with the blockade of the kinin B 1 receptor protein overexpression in the gastrocnemius muscle and its composition in fatty acids notably in linoleic and oleic acids [ 42 ] in glucose-fed rats. This is in accordance with a previous study [ 34 ], which has reported that four weeks of treatment with argan oil blunted hyperglycemia and hyperinsulinemia in obese insulin-resistant rats.…”
Section: Discussionmentioning
confidence: 99%
“…Corn oil was found to be safe with no clinical signs or toxicity at 5 mL kg −1 day −1 for 12 weeks in treated SD rats [ 56 ]. We compared corn oil to argan oil because they contain approximately the same composition of fatty acids with the exception that argan oil also contains tocopherols, sterols and, to lesser extent, melatonin [ 42 ]. The dose of argan and corn oil was selected on the basis of our previous study [ 33 ], which failed to show any negative effects when administered for a period of 5 weeks in this model and on the basis of other studies using 5 mL kg −1 day −1 chronically administered by oral gavage in other animal models [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…Argan oil is capable of inhibiting processes induced by 7KC: loss of cell adhesion; cell growth inhibition; increased plasma membrane permeability; mitochondrial, peroxisomal and lysosomal dysfunction and the induction of oxiapoptophagy (OXIdation + APOPTOsis + autoPHAGY) in oligodendrocytes [111].…”
Section: Cytoprotector Effects Of Vegetable Oilmentioning
confidence: 99%